Intratumoral T-cell repertoires in DNA mismatch repair-proficient and -deficient colon tumors containing high or low numbers of tumor-infiltrating lymphocytes. (31st December 2022) - Kim, Jin K.; Chen, Chin-Tung; Keshinro, Ajaratu; Khan, Asama; Firat, Canan; Vanderbilt, Chad; Segal, Neil; Stadler, Zsofia; Shia, Jinru; Balachandran, Vinod P.; Weiser, Martin R.
ABSTRACT: Colon tumors with deficient DNA mismatch repair (dMMR) are generally infiltrated by T cells more densely than tumors with proficient mismatch repair (pMMR). However, high numbers of tumor-infiltrating lymphocytes (TILs) are found in select pMMR tumors, and low numbers of TILs are seen in select dMMR tumors. In this study, we compared T-cell repertoires in 20 pMMR and 27 dMMR colon tumors with high and low TIL counts. We found that T cells in dMMR tumors are more clonal and their repertoire is less rich compared with T cells in pMMR tumors. In the dMMR group, T cells in TIL-high tumors were more clonal and their repertoire was less rich compared with T cells in TIL-low tumors, but in the pMMR group, T-cell diversity in TIL-high tumors was comparable to T-cell diversity in TIL-low tumors. These findings suggest that T cells clonally expand in dMMR tumors, possibly in response to MMR deficiency-induced tumor neoantigens.